The Combination of NLCR and Enhances the Sepsis-3 Strategy - Pranggono, Emmy Hermiyanti; Aini, Endah Nurul; Sumardi, Uun; Hartranti, Yovita; Sugianli, Adhi Kristianto (Folia Medica Indonesiana, 2022)
Highlights: • The combination of NLCR and PLR will improve the ability to distinguish infection rather than noninfection in the emergency setting for early antibiotic prescribing as well as the sepsis-3 strategy. • The diagnostic value of PLR in adult bacterial sepsis patients has never been studied. Abstract: According to Sepsis-3, antibiotics should be administered in the first hour of diagnosis of sepsis. Still, there is difficulty in differentiating between bacterial and nonbacterial infections and a lack of a rapid diagnostic tool to distinguish them. This study evaluated the diagnostic value of NLCR and PLR in suspected bacterial sepsis. The diagnostic value of PLR in adult bacterial sepsis patients has never been studied. This study was a retrospective study from the medical record of Dr. Hasan Sadikin Hospital Bandung. All patients at age â‰¥ 18 years diagnosed with sepsis based on ICD-10 code and qSOFA â‰¥ 2 were included. We calculated sensitivity, specificity, NPV, PPV, positive LR, and AUC of NLCR and PLR. There were 177 patients included in this study. The sensitivity of NLCR was 69.5%, specificity was 34.7%, NPV was 56.9%, PPV was 47.9%, and LR+ was 1.06, while the sensitivity of PLR was 62.2%, specificity was 38.9%, NPV was 54.4%, PPV was 46.8%, and LR+ was 1.02. We obtained cut-off values for NLCR 11.06, AUC 0.500, PLR 222.41, and AUC 0.497. The low value of AUC NLCR and PLR was due to prior antibiotic use. The combination of NLCR and PLR had higher positive LR (1.16) and specificity (54.7%), and also, according to NLCR, we had the highest sensitivity (69.5%). The combination of NLCR and PLR enhances the sepsis-3 strategy because it can be used as screening tools for bacterial sepsis, and antibiotics can also be administered in the first hour of managing sepsis, particularly in the emergency ward.